Isolation of the Binding Protein of Periplocoside E from BBMVs in Midgut of the Oriental Amyworm Mythimna separata Walker (Lepidoptera: Noctuidae) through Affinity Chromatography - Mingxing Feng; Zhenyu He; Yuanyuan Wang; Xiufang Yan; Jiwen Zhang; Zhaonong Hu; Wenjun Wu (Toxins, 2016)
Periplocosides, which are insecticidal compounds isolated from the root bark of Periploca sepium Bunge, can affect the digestive system of insects. However, the mechanism though which periplocosides induces a series of symptoms remains unknown. In this study, affinity chromatography was conducted by coupling periplocoside E-semi-succinic acid ester with epoxy amino hexyl (EAH) sepharose 4B. Sodium dodecyl sulfonate-polyacrylamide gelelectrophoresis (SDS-PAGE) was performed to analyze the fraction eluted by periplocoside E. Eight binding proteins (luciferin 4-monooxygenase, aminopeptidase N, aminopeptidase N3, nicotinamide adenine dinucleotide health (NADH) dehydrogenase subunit 5, phosphatidylinositol 3-phosphate 3-phosphatase myotubularin, actin, uncharacterized family 31 glucosidase KIAA1161, and 2OG-Fe(2) oxygenase superfamily protein) were obtained and identified through liquid chromatography/quadrupole-time of flight-mass spectrometry (LC/Q-TOF-MS) analysis of the midgut epithelium cells of Mythimna separata larvae. Aminopeptidase N and N3 are potential putative targets of periplocosides. This study establishes the foundation for further research on the mechanism of action and target localization of periplocosides in agricultural pests.